Discussion Club. Succession - Tkacheva, Marina (project baikal, 2021)
Participants and guests of the Festival discussed the problems of cultural and architectural succession, the relationship between the history of cities and their current state, and the fate of architectural monuments of the 20th century. They touched upon the issues of traditions and innovations in the social and architectural practices and spoke about the status of the monuments of the 20th century and their preservation.
Keywords: tradition; history of architecture; design; architectural monuments; restoration; architectural norms; regional schools